Birds and Seals of the South Shetland Islands (Maritime Antarctic Region) - Müller-Schwarze, Dietland (IWF (Göttingen), 1979)
Brooding Cycle of the gentoo penguin species. Presentation of the following birds and seals in their habitat: blue-eyed shag; sheathbill; brown skua; giant petrel; cape pigeon; Antarctic tern; southern fur seal; crabeater seal; weddell seal; southern elephant seal.